2016
DOI: 10.1167/iovs.15-18524
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Chemokine Secretion and Monocyte Migration by Human Choroidal Melanocytes in Response to Proinflammatory Cytokines

Abstract: These results showed that normal and activated HCMs are immunologically active by secreting chemokines, and that HCMs are able to attract monocytes in addition to inhibiting T-cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…However, recently we have demonstrated that native choroidal melanocytes may harbor similar functionality including secretion of chemokines and suppression of T cell activation. 15 Systemically increased levels of IFN-c from systemic virus infection in rodents has been shown to induce a transient subretinal accumulation of retinal microglia, 16 which indicates that systemic inflammation contributes to the immune status of the chorioretinal interface. The transcriptional response of the choroidal/RPE interface to systemic inflammation has, however, not been explored before.…”
mentioning
confidence: 99%
“…However, recently we have demonstrated that native choroidal melanocytes may harbor similar functionality including secretion of chemokines and suppression of T cell activation. 15 Systemically increased levels of IFN-c from systemic virus infection in rodents has been shown to induce a transient subretinal accumulation of retinal microglia, 16 which indicates that systemic inflammation contributes to the immune status of the chorioretinal interface. The transcriptional response of the choroidal/RPE interface to systemic inflammation has, however, not been explored before.…”
mentioning
confidence: 99%
“…The monocyte role was not explored in depth in the present work. However, monocyte migration towards uveal melanocytes after being in contact with conditioned medium from activated T cells that contains increased IFN-γ and TNF-α has been described in vitro 48 . T cells produce those cytokines after T cell receptor stimulation and induce monocyte production of GMCSF.…”
Section: Resultsmentioning
confidence: 99%
“…Another gene, whose expression in the LPS‐stimulated lightly pigmented melanocytes was substantially higher (over 100‐fold at the mRNA transcript level and nearly 2‐fold at the protein level) than in the heavily pigmented cells, was that encoding CCL2 chemokine. CCL2 (monocyte chemotactic protein 1; MCP‐1) is one of the key chemokines that regulate migration and infiltration of monocytes, macrophages and lymphocytes, and has a role in chronic inflammation . Moreover, it stimulates proliferation and migration of endothelial cells and may contribute to the mechanism of increased pathological angiogenesis in lighter skin.…”
Section: Discussionmentioning
confidence: 99%
“…After the LPS treatment, HEMn‐DP secreted much more CXCL8 (IL‐8) than HEMn‐LP, despite the higher expression showed by the latter cells at the mRNA level. The chemokine is involved in the acute inflammatory response in vivo and exhibits a chemotactic activity for neutrophils, T cells, fibroblasts, endothelial cells and melanocytes in vitro . Miniati et al observed increased release of CXCL8 from human melanocytes in response to TNF‐α and IL‐1β, and elevated CXCL8 gene expression in the lesional skin of patients with new‐onset and active vitiligo.…”
Section: Discussionmentioning
confidence: 99%